Forensic science under siege : the challenges of forensic laboratories and the medico-legal death investigation system - Pyrek, Kelly (Elsevier / Academic Press, 2007)
Forensic science laboratories' reputations have increasingly come under fire. Incidents of tainted evidence, false reports, allegations of negligence, scientifically flawed testimony, or - worse yet - perjury in in-court testimony, have all served to cast a shadow over the forensic sciences. Instances of each are just a few of the quality-related charges made in the last few years. Forensic Science Under Siege is the first book to integrate and explain these problematic trends in forensic science. The issues are timely, and are approached from an investigatory, yet scholarly and research-driven, perspective. Leading experts are consulted and interviewed, including directors of highly visible forensic laboratories, as well as medical examiners and coroners who are commandeering the discussions related to these issues. Interviewees include Henry Lee, Richard Saferstein, Cyril Wecht, and many others. The ultimate consequences of all these pressures, as well as the future of forensic science, has yet to be determined. This book examines these challenges, while also exploring possible solutions (such as the formation of a forensic science consortium to address specific legislative issues). It is a must-read for all forensic scientists. * Provides insight on the current state of forensic science, demands, and future direction as provided by leading experts in the field * Consolidates the current state of standards and best-practices of labs across disciplines * Discusses a controversial topic that must be addressed for political support and financial funding of forensic science to improve.